Effect of Oleogelation Temperature on Physicochemical Properties and Stability of Peanut Oil Oleogel (Arachis hypogaea L.) - Wangsa, Chrisnadya Putri; Fitriani, Amalia; Setiowati, Arima Diah; Hidayat, Chusnul (agriTECH, 2024)
Oleogelation is a method to transform liquid oil into solid fats without altering the fatty acid profile. Compared to hydrogenation, oleogelation requires a relatively simple process and does not produce trans fats. In oleogelation, temperature has a crucial role in affecting the properties of oleogel. Therefore, this study aimed to examine the effect of oleogelation temperature on the physicochemical properties and stability of peanut oleogel. In this study, peanut oil oleogel was formed at 70 °C, 80 °C, and 90 °C using 3% beeswax as oleogelator agent. The best oleogel obtained was stored for 40 days and evaluated for its stability every 10 days followed by testing as a shortening replacer in a cake. The results showed that the higher oleogelation temperature, the greater the hardness and oil binding of oleogel, leading to lower acid and peroxide values. The best oleogelation temperature was obtained at 90 °C with hardness, oil binding capacity, acid, and peroxide values of 0.08±0.01N, 98.31±0.39%, 0.70±0.03 mg KOH/g, and 22.61±0.33 mek O2 /kg, respectively. During 40 days of storage, the hardness and oil binding capacity decreased while the acid, peroxide, and TBA values increased. Additionally, the crystal structure of peanut oil oleogel was affected during storage. The application in cake resulted in lower viscosity of cake batter and a higher yellow index compared to the control (shortening), but the texture profile of cake formulated with oleogel and shorthening (contorl)  was not significantly different. This implied that shortening replacement with peanut oil oleogel in baked products was feasible.